2019
DOI: 10.3390/su11247125
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Lighting-Retrofit Versus Dedicated Luminaires-Light Versus Power Quality

Abstract: For the next few years millions of fluorescent luminaires will become waste and will be replaced by light-emitting diodes-LED luminaires. According to the Cost European Cooperation in Science & Technology Program, the next step will be shifting from sustainability to regeneration (enabling social and ecological systems to maintain a healthy state and to evolve); to reach this point, a is circular economy becomes necessary. The Technical University of Cluj-Napoca's Lighting Engineering Laboratory-LEL-is the mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…For the tested LED luminaires, the harmonic deformation on the supply voltage, with higher values but still within the standard limits, will cause an increase in the current harmonic distortion generated by the LED luminaires. Different studies [18][19][20] have addressed the possibility of retrofitting existing luminaires with LEDs with the purpose of reducing waste materials and reusing different components of the existing luminaires. It was concluded that the selection of the proper lighting gear is crucial during the retrofit design phase, not only for satisfying the requirements imposed by regulations on average illuminance and uniformity but also for their energy performance and power quality [20].…”
Section: Introductionmentioning
confidence: 99%
“…For the tested LED luminaires, the harmonic deformation on the supply voltage, with higher values but still within the standard limits, will cause an increase in the current harmonic distortion generated by the LED luminaires. Different studies [18][19][20] have addressed the possibility of retrofitting existing luminaires with LEDs with the purpose of reducing waste materials and reusing different components of the existing luminaires. It was concluded that the selection of the proper lighting gear is crucial during the retrofit design phase, not only for satisfying the requirements imposed by regulations on average illuminance and uniformity but also for their energy performance and power quality [20].…”
Section: Introductionmentioning
confidence: 99%
“…Climate and user responses along with monitoring and supervision are some of the basic functions of smart buildings [1], which adapt to climatic conditions to minimize energy demand and generate energy to supply their energy consumption [2], and monitoring and supervision are necessary to control loads and set comfort settings [3]. However, to achieve the aim of adequate energy efficiency it is necessary to use modern lighting systems (LED and compact fluorescent lamps) [4,5], as well as numerous types of non-linear loads or DC appliances that need individual rectifiers to facilitate the connection of the equipment 2 of 19 to the AC grid [6], and of course, to integrate the use of renewable energies, especially photovoltaic technology.…”
Section: Introductionmentioning
confidence: 99%